Existence of Positive Solutions for Singular Fourth Order Coupled System with Sign Changing Nonlinear Terms (Communications in Mathematical Research, 2021)
This paper deals with the existence of positive solutions to a singularfourth order coupled system with integral boundary conditions. Since the nonlinearterms $f$, $g$ may change sign or be singular at $t = 0$ or $t = 1$, the authors make apriori estimates to overcome some difficulties and apply Guo-Krasnoselskii fixed pointtheorem to prove the existence of solutions of the system under suitable assumptions.Finally, some examples to illustrate the main results are given.
Keywords: fixed point theorem; positive solution; integral boundary condition.